The Usage and Limitations of Comparative Law and the Methodology of International Criminal Procedure - Vasiliev, Sergey (Revista Eletrônica de Direito Penal, 2019)
The Usage and Limitations of Comparative Law and the Methodology of International Criminal Procedure.